The Development of Impulse and Momentum E-Module with Authentic Learning Content in Cooperative Learning Model Syntax - Mahardika, Andi Ichsan; Arifuddin, Muhammad; Juhroh, Siti (Jurnal Pendidikan Progresif, 2022)
The Development of Impulse and Momentum E-Module with Authentic Learning in Cooperative Learning Model Syntax. E-modules should be able to accommodate a learning syntax that supports student activity. Therefore, the general objective of this research is to produce an impulse and momentum e-module product containing authentic learning in the cooperative learning model syntax, as well as describing its feasibility. The type of research is research and development used  the ADDIE model within 17 students. Data obtained through instrument used is e-module validation sheet, student response questionnaire, and learning outcomes test. The results showed that: (1)  validity of e-module scored by 3.25 categorized as valid, (2) practicality of E-Module scored by 2.94 categorized as practical, (3) effectiveness of e-module scored by 0.57 categorized as medium. It can be concluded that e-module impulse and momentum contained authentic learning through cooperative learning model is eligible to be used in learning process. Keywords: e-module, impulse and momentum, authentic learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202214